The contribution of skin glycosaminoglycans to the regulation of sodium homeostasis in rats - Sugár, D; Agócs, R; Tatár, E; Tóth, G; Horváth, P; Sulyok, E; Szabó, A. J (Physiological research, 2018)
The glycosaminoglycan (GAG) molecules are a group of high molecular weight, negatively charged polysaccharides present abundantly in the mammalian organism. By their virtue of ion and water binding capacity, they may affect the redistribution of body fluids and ultimately the blood pressure. Data from the literature suggests that the mitogens Vascular Endothelial Growth Factor (VEGF)-A and VEGF-C are able to regulate the amount and charge density of GAGs and their detachment from the cell surface. Based on these findings we investigated the relationship between the level of dietary sodium intake, the expression levels of VEGF-A and VEGF-C, and the amount of the skin GAGs hyaluronic acid and chondroitin sulfate in an in vivo rat model. Significant correlation between dietary sodium intake, skin sodium levels and GAG content was found. We confirmed the GAG synthesizing role of VEGF-C but failed to prove that GAGs are degraded by VEGF-A. No significant difference in blood pressure was registered between the different dietary groups. A quotient calculated form the ion and water content of the skin tissue samples suggests that - in contrast to previous findings - the osmotically inactive ions and bound water fractions are proportional.
Keywords: Animals; Sodium; náhodné rozdělení; Vascular Endothelial Growth Factor A; potkani Wistar; Skin; zvířata; glykosaminoglykany; sodík dietní; Random Allocation; Sodium, Dietary; Female; Rats; Rats, Wistar; sodík; kůže; krysa rodu Rattus; Glycosaminoglycans; ženské pohlaví; vaskulární endoteliální růstový faktor A